2016
DOI: 10.1111/hcre.12084
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Person-Culture Fit in Chinese Students' Cultural Adjustment in the United States: A Galileo Mental Model Approach

Abstract: This article used a Galileo multidimensional scaling model to explain how intercultural communication affected sojourners' wellbeing in their host culture through the convergence of the mental models between sojourners and host nationals with whom the sojourners communicated. Participants were 126 sojourning Chinese in the United States and 30 associated domestic Americans. Data were collected shortly after the Chinese sojourners arrived in the United States and again 3 months later. A measure of person-cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…These outcomes included organizational commitment, extra-role behavior and employee health/burnout, among others. This is in line with research that has shown a relationship between work value congruence and OCB (Cole et al , 2013), affective commitment (Astakhova, 2016; Ryu, 2015) and psychological well-being (Zhu et al , 2016).…”
supporting
confidence: 91%
“…These outcomes included organizational commitment, extra-role behavior and employee health/burnout, among others. This is in line with research that has shown a relationship between work value congruence and OCB (Cole et al , 2013), affective commitment (Astakhova, 2016; Ryu, 2015) and psychological well-being (Zhu et al , 2016).…”
supporting
confidence: 91%
“…Communication is a significant problem that expatriates worry about, leading to cultural barriers (Zhu & et al, 2016). However, SAMSUNG, as the top company in South Korea, solves this difficulty correctly.…”
Section: Trainingmentioning
confidence: 99%
“…There are negative reinforcements that could also lead to changes in attitude towards positive learning outcomes (Hoadley & Kali, 2019;Manimaran et al, 2016). Changes in the way they perceive things may vary from different phases of their adjustment and adapting the culture unconsciously behind those experiences (Chao et al, 2017;Jones & Bond, 2019;Lent et al, 2015;Zhu et al 2016). From the study of Ramirez and Dizon (2014) also noted that attitude of the engineering students has subjective element from psychological point of view.…”
Section: Introductionmentioning
confidence: 99%